Mixed foliate CR-submanifolds in a complex hyperbolic space are non-proper - Bang-Yen Chen; Bao-Qiang Wu (International Journal of Mathematics and Mathematical Sciences, 1988)
It was conjectured in [1 II] (also in [2]) that mixed foliate CR-submanifolds in a complex hyperbolic space are either complex submanifolds or totally real submanifolds. In this paper we give an affirmative solution to this conjecture.